Student support services in open universities in India: a comparative analysis - V, Manzoor Babu (International Multidisciplinary Research Journal, 2012)
Distance education is an effective tool for the provision of education to a heterogeneous group of learners as well as an alternative channel to democratize education all over the world. In such a stream the importance of student support services are unquestionnable. The present study examines the existing scenario of student support services provided in the country, and learners perception regarding the same. The study is conducted on students of three selected Open Universities in the country, viz, Indira Gandhi Open University, BR Ambedkar Open University and Karnataka State Open University. Study reveals the pathetic situation of student support services provided by the Open Universities in the country. It also throws light about the perception of learners about various student support services provided in Open Universities in the country.